(untitled) - Bronowski, J. (New York, 1960)
This book is a study of the developing ideas from the Renaissance to the opening of the nineteenth century. It is intellectual history in the largest sense, not confined to ideas in one or a few fields, but covering the whole spectrum of Western intellectual activity during the four centuries when the world was transformed from medieval to modern. An important feature of the book is its stress on the interplay of ideas from different fields. In particular, the authors give more attention than is usual to the ideas of science, to the movements of literary style, and to the innovations in the arts. The book is divided into three parts: Part One: The Expanding World. Part Two: The Age of Reasoned Dissent. Part Three: The Great Revolution. "This is a valuable and brilliant book . . ." C.P. Snow
Keywords: Phylosophy, modern,Civilization